Black Folk Religion in Black Holiness Pentecostalism: Spiritual Formation Among Black Pentecostals - Harris, Antipas L. (Journal of pentecostal theology, 2019)
This essay seeks to understand theological rudiments embedded in traditional black Pentecostal spirituality to enhance spiritual formation in contemporary black Pentecostalism. Its conclusions contribute to a praxis-oriented discourse on the black folk religious tradition, black holiness Pentecostalism, and a contemporary ethnically diverse society in which black people continue to suffer disproportionately. The salient question is, what transformative proposals emerge from black spiritual praxis', or a conversation between black religious heritage and contemporary black America? While this essay does not attempt to draw conclusions for contemporary lived practice, it unearths jewels in black Pentecostal spirituality that deepen insight into faith formation in an increasingly diverse society wherein the dominant formational paradigms have lodged within the tunnel vision of Western categories.